Sistem Kemasyarakatan dalam Kumpulan Puisi Kanaya Karya Rini Intama - Emil Septia; Armet Armet (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: The Community System in Rini Intama's Kanaya Poetry Collection. This study aims to describe the form of local wisdom (elements of the social system) in the collection of Kanaya poems by Rini Intama. This type of research is qualitative research. The method used in this study is the conten analysis method (content analysis). The data in this study is in the form of words, sentences, and discourses related to local wisdom forms in the collection of Kanaya poems by Rini Intama. The source of data in this study is a collection of Kanaya poems by Rini Intama. The results showed that there is a cultural element of the social system contained in the form of rituals, a royal system that tells that there is a form of government. In Kanaya's collection of poems, the poet also explains how a woman's struggle in maintaining and caring for a tradition through puppetry and customs that have existed from the beginning of the formation of the Sundanese land. As well as reiterating to the community in order to preserve the conceptions of ancestral culture through arrays and stanzas in each poem.